INTRUSION DEFENSE MECHANISM USING ARTIFICIAL IMMUNE SYSTEM IN CLOUD COMPUTING (CLOUD SECURITY USING COMPUTATIONAL INTELLIGENCE) - L, Santhanalakshmi; R, Sakkaravarthi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Cloud is a general term used in organizations that host various service and deployment models. As cloud computing offers everything a service, it suffers from serious security issues. In addition, the multitenancy facility in the cloud provides storage in the third party data center which is considered to be a serious threat. These threats can be faced by both self-providers and their customers. Hence, the complexity of the security should be increased to a great extend such that it has an effective defense mechanism. Although data isolation is one of the remedies, it could not be a total solution. Hence, a complete architecture is proposed to provide complete defense mechanism. This defense mechanism ensures that the threats are blocked before it invades into the cloud environment. Therefore, we adopt the mechanism called artificial immune system which is derived from biologically inspired computing. This security strategy is based on artificial immune algorithm. Â 